Minimally invasive aesthetic procedures in young adults - Wollina U; Goldman A (Dove Medical Press, 2011)
Uwe Wollina1, Alberto Goldman21Department of Dermatology and Allergology, Academic Teaching Hospital Dresden-Friedrichstadt, Dresden, Germany; 2Clinica Goldman, Porto Alegre, Rio Grande du Sul, BrazilAbstract: Age is a significant factor in modifying specific needs when it comes to medical aesthetic procedures. In this review we will focus on young adults in their third decade of life and review minimally invasive aesthetic procedures other than cosmetics and cosmeceuticals. Correction of asymmetries, correction after body modifying procedures, and facial sculpturing are important issues for young adults. The implication of aesthetic medicine as part of preventive medicine is a major ethical challenge that differentiates aesthetic medicine from fashion.Keywords: acne scars, ice pick scars, boxcar scars, fillers